Late Capsular Hematoma after Prosthesis Removal Following Aesthetic Breast Augmentation: A Case Report - Si Hyun Park (Archives of Aesthetic Plastic Surgery, 2017)
Late capsular hematoma formation after augmentation mammoplasty with an implant is a very rare complication. Some mechanisms explaining late capsular hematoma formation have been reported; it is thought to be associated with capsular contracture, textured implants, and the use of corticosteroid and anticoagulant agents. However, no reports of late capsular hematoma formation after prosthesis removal have been published. Herein, we report a case of late capsular hematoma formation after the removal of a prosthesis 10 years previously, following augmentation mammoplasty.